Lina and Serge the love and wars of Lina Prokofiev - Morrison, Simon Alexander 1964- (Houghton Mifflin Harcourt, 2013)
Chronicles the life of Lina Prokofiev, who followed her composer husband to Stalinist Russia, only to be left for another woman and incarcerated for eight years